Radiation dose comparison in CT thorax, CT abdomen and CT thorax-abdomen-pelvis (TAP) using 640-and 160-slice computed tomography (CT) scanners - Gan, Ying Shen; Akmal Sabarudin; Hamzaini Abdul Hamid; Mazli Mohd Zain; Muhammad Khalis Abdul Karim; Khadijah Mohamad Nassir (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study was carried out to compare the effective dose, size specific dose estimation (SSDE) and scan length between genders and between CT scanner with different slice number. A total of 245 set data of radiation dose and scan length for CT scanning procedure involving thorax, abdomen and pelvis regions were obtained retrospectively for comparisons. 111 patients (60 males and 51 females) were scanned using 160-slices CT scanner while 134 patients (71 males and 63 females) were scanned using 640-slices CT scanner. Generally, there were no significant differences in the radiation dose and scan length among genders. However, differences for SSDE in CT thorax and CT thorax-abdomen-pelvis (TAP) protocols exist whereby in CT thorax protocol, 640-slices CT scanner had a significantly higher value of SSDE (9.06±2.67 mGy) than that in 160-slices CT scanner (7.82±1.33 mGy). Similarly to the CT TAP protocol, whereby 640-slices CT scanner had a significantly lower value in SSDE (9.17±1.59 mGy) than that in 160-slices CT scanner (10.76±3.72 mGy). In conclusion, there was no significant difference in the radiation dose and scan length between genders but significant difference was only observed in SSDE due to the presence of body size variation among the study population especially in different CT scanners.